Policy options for advancing seed systems for vegetatively propagated crops in Vietnam - Gatto, M.; Le, Dung Phuong; Pacillo, Grazia; Maredia, Mywish K.; Hareau, Guy; Spielman, David J.; Labarta, Ricardo Antonio (International Potato Center, 2020)
Seed systems for vegetatively propagated crops (VPCs) are frequently governed by a regulatory blueprint designed for major cereal crops. This approach tends to disregard the distinct biological characteristics of VPCs, in turn limiting farmers’ access to high-quality planting material and increasing the risk of pest and disease transmission. In this paper, we ask what type of regulatory framework is appropriate for improving farmers’ access to quality VPC planting material, and what the costs, benefits, risks, and unintended consequences are of alternative regulations. We explore this in the context of cassava and potato in Vietnam through secondary data and document analysis, key informant interviews, and focus group discussions. Findings indicate that despite a regulatory regime that imposes strict rules on the production and trade of planting material for VPCs, the market is largely unregulated due to weak enforcement capacity. In the absence of regulatory enforcement, however, producers and traders of VPC planting material signal quality to farmers through trust, reputation, and long-term relationships. Though effective at a small and localized scale, these informal systems are unlikely to accommodate the plans for rapid expansion of the cassava and potato sectors outlined in the Government of Vietnam’s strategy for growth and development. Nor are they likely to prove effective in managing increases in pest and disease pressures that result from cross-border trade, climate change, or other factors. We discuss alternative policy approaches and argue that the most appropriate policy regime requires that a careful balance be struck between a permissive regime at the local level and strict regulatory surveillance and enforcement at the national and regional level.